Penggunaan Serat Pandan Duri (Pandanus tectorius) Sebagai Pengganti Fiber Glass pada List Profil Gypsum - Assyifa Rahmadanisa; Puji Dewi Lestari; Shifa Fauziyah; H Hartono (Universitas Diponegoro, 2023)
The gypsum profile list is a material made from gypsum flour which in its manufacture uses fiberglass as reinforcement to strengthen the gypsum profile list. Currently, natural fibers are being developed so that they can be alternative materials to replace fiberglass or synthetic fibers which are difficult to decompose. One of the natural fibers is pandan leaf fiber which is included in the Pandanaceae family such as pandanus thorns. Thorn pandanus are known to have long, strong, and flexible leaves. The purpose of this study was to determine whether thorn pandanus fiber with certain variations can be used as a substitute for fiberglass in the manufacture of gypsum profile lists. In addition to knowing the composition of the mixture between thorn pandanus fiber and gypsum flour in order to obtain the optimum composition. This research refers to SNI 01-4449-2006 regarding fiberboard for testing density, thickness expansions, and flexural strength while testing water absorption using FAO standards. Based on the test results, it was found that the most optimum composition of the gypsum profile list mixture was found in sample B with 99% gypsum flour: 1% thorn pandanus fiber which had a density value of 0.805 g/cm3, a water absorption value of 27.87%, a thickness expansion of 1.92 %, and flexural strength 10410.7 kgf/cm2 due to the results of density, thickness expansion, and flexural strength complies with SNI 01-4449-2006 standards regarding fiberboard while the water absorption test complies with FAO standards. Keywords: gypsum profile list, thorn pandanus fiber, gypsum flour